Impact of the internet, social media on children: what is the role of pediatricians? - Johan Christian Silaen (Jurnal EduHealth, 2024)
During the child and adolescent years, internet and social media use has a significant impact on social, emotional and mental health development. UN research shows that 47 percent of the world's population uses the internet, with one-third of them under the age of 18. Intense social media use, such as checking more than 10 times per day, can have negative impacts, including threats to personal safety, sleep disturbances and addiction. However, the internet also provides extensive access to information and strengthens social relationships. The role of pediatricians is crucial in educating parents and providing wise guidance on children's use of the internet and social media, including supervising, setting limits, and providing information on cyberbullying and sexual harassment. With proper supervision, children and adolescents can utilize the internet and social media positively without harming their mental health and development.